Investigation on the Best Conditions for Purification of Multiwall Carbon Nanotubes - Marjani, Azam; Shirazi, Yaser; Shirazian, Saeed (Asian Journal of Chemistry, 2011)
Multiwall carbon nanotubes (MWCNTs) were synthesized using cyclohexanol, ferrocene and nitrogen as carbon source, catalyst and carrier gas, respectively. Carbon nanotubes purification was performed by oxidation and acid treatment. Characterization of carbon nanotubes before and after purification was carried out using SEM, TEM and Raman spectroscopy and show that purification can reduce amorphous carbon and metal particles significantly. Furthermore, different acid treatment [HNO3/H2SO4 (1/3), (c) HNO3/H2SO4 (1/1), (d) 8M HCl and (e) 8M HNO3] demonstrated that 8M HNO3 can decrease impurities without destroying the structure of carbon nanotubes.